Healthy Drinks of Javanese Clover and Ginseng Based on Organoleptic Tests - Ahmad Saiful Arifin; Mohamad Nasiruidin; Ana Mariatul Khiftiyah (AGARICUS: Advances Agriculture Science & Farming, 2021)
Clover is generally used as a remedy for sore throat, mouth sores, fever, and shortness of breath. Researchers have the idea of ​​combining with Javanese ginseng leaves so that they can produce drinks that are rich in benefits. This research was conducted to determine the process of making a healthy drink and organoleptic test. This study uses the RAL method with five levels and four repetitions, so that in this study twenty experimental units were obtained. With a combination of K1 is clover 30%; ginseng 70%, K2 is clover 40%; ginseng 60%, K3 is clover 50%; ginseng 50%, K4 is clover 60%; ginseng 40%, K5 is clover 70%; ginseng 30%. Data analysis used descriptive, qualitative methods. The process of making clover ginseng healthy drink by mashing clover leaves and ginseng leaves, filtering, cooking until boiling then adding sugar, stirring slowly over medium heat, and speeding up the mix when it has clotted to get fine crystals. The cause of the color change is influenced by the crystallization temperature. The aroma of sugar caramel in the healthy drink of clover and ginseng and the taste is sweet. The acceptance variable is in great demand in the combination of 50% clover leaf K3 and 50% ginseng leaf.